Biographical Memoirs: Volume 78 - National Academy of Sciences (The National Academies Press, 2000)
Biographic Memoirs: Volume 78 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 76 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 76 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

The National Academy of Sciences: The First Hundred Years, 1863-1963 - National Academy of Sciences (The National Academies Press, 1978)
Among the oldest and most enduring of American institutions are those that have been devoted to the encouragement of the arts and the sciences. During the nineteenth century, a great many scientific societies came and went, and a few in individual disciplines achieved permanence. But the century also witnessed the founding of three major organizations with broadly interdisciplinary interests: the Smithsonian Institution in 1846; the Association of American Geologists and Naturalists, which in 1848 became the American Association for the Promotion (later, Advancement) of Science; and the National Academy of Sciences in 1863. The founding of the National Academy of Sciences represented a momentous event in the history of science in the United States. Its establishment in the midst of a great civil war was fortuitous, perhaps, and its early existence precarious; and in this it mirrored the state of science at that time. The antecedents of the new organization in American science were the national academies in Great Britain and on the Continent, whose membership included the principal men of science of the realm. The chartering of academies under the auspices of a sovereign lent the prestige and elements of support and permanence the scientists sought, and in return they made their scientific talents and counsel available to the state. The National Academy of Sciences: The First Hundred Years, 1863-1963 describes the National Academies from inception through the beginning of the space age. The book describes the Academies' work through different periods in history, including the Postbellum years, World War I, the Great Depression, and World War II.
Keywords: Policy for Science and Technology

Biographical Memoirs: Volume 80 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 80 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 70 - National Academy of Sciences (The National Academies Press, 1996)
Biographic Memoirs: Volume 70 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

A Relationship Restored: Trends in U.S.-China Educational Exchanges, 1978-1984 (The National Academies Press, 1986)
In what The Wall Street Journal calls "the first comprehensive analysis of Sino-American educational exchanges," this volume provides information on the numbers and attributes of American and Chinese students and scholars who have moved between China and the United States since 1978. This book not only supplies quantitative data on their fields of study, length of stay, and financial resources, but also discusses such qualitative issues as the problems students and scholars have encountered in carrying out their work, the adequacy of their preparation, the "reabsorption" process that students and scholars from China face upon their return home, and the impact of the exchange process on fields of study in both countries.
Keywords: Education

The Positive Sum Strategy: Harnessing Technology for Economic Growth - Landau, Ralph; Rosenberg, Nathan (The National Academies Press, 1986)
This volume provides a state-of-the-art review of the relationship between technology and economic growth. Many of the 42 chapters discuss the political and corporate decisions for what one author calls a "Competitiveness Policy." As contributor John A. Young states, "Technology is our strongest advantage in world competition. Yet we do not capitalize on our preeminent position, and other countries are rapidly closing the gap." This lively volume provides many fresh insights including "two unusually balanced and illuminating discussions of Japan," Science noted.
Keywords: Industry and Labor

Biographical Memoirs: Volume 74 - National Academy of Sciences (The National Academies Press, 1998)
Biographic Memoirs: Volume 74 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography; Biology and Life Sciences

Biographical Memoirs: Volume 48 - National Academy of Sciences (The National Academies Press, 1976)
Biographic Memoirs: Volume 48 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 44 - National Academy of Sciences (The National Academies Press, 1974)
Biographic Memoirs: Volume 44 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 82 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 82 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 46 - National Academy of Sciences (The National Academies Press, 1975)
Biographic Memoirs: Volume 46 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

A History of the First Half-Century of the National Academy of Sciences: 1863-1913 (The National Academies Press, 1913)
The National Academy of Sciences is the third oldest American institution, being established after the Smithsonian Institute and the American Association for the Promotion of Science. The Academy dates back to 1863, right in the midst of the American Civil War. Fortunately for the time, the Academy was vital to the development of the war in favor of the Union through its establishment of much needed scientific advancements and insight tantamount to those of the academies in Great Britain and the rest of Europe despite the involvement of science's most primary men. Since then, the Academy has served as a scientific adviser to the government, an adviser greatly appreciated by the government. The Academy's recommendations have been adopted, its findings accepted, and its investigations used to better advance the nation as a whole. A History of the First Half-Century of the National Academy of Sciences: 1863-1913 (1913) illustrates the Academy's history from its creation to the appointment of Woodrow Wilson as president. The book features a detailed look into the founding and forming of the Academy; the annals of the academy including the classifications of membership in 1892; lists of those involved with the Academy including officers and foreign associates; the Academy's publications, and more.
Keywords: Policy for Science and Technology; Explore Science

Ecological Risks: Perspectives from Poland and the United States - National Academy of Sciences (The National Academies Press, 1990)
Keywords: Environment and Environmental Studies

Biographical Memoirs: Volume 83 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 83 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 91 - National Academy of Sciences (The National Academies Press, 2009)
Biographic Memoirs Volume 91 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Science at the Frontier - National Academy of Sciences (The National Academies Press, 1992)
Science at the Frontier takes you on a journey through the minds of some of the nation's leading young scientists as they explore the most exciting areas of discovery today. Based on the second Frontiers of Science symposium sponsored by the National Academy of Sciences, this book describes recent accomplishments and new directions in ten basic fields, represented by outstanding scientists convening to discuss their research. It captures the excitement and personal quality of these exchanges, sometimes pointing to surprising connections spanning the boundaries of traditional disciplines, while providing a context for the reader that explains the basic scientific framework for the fields under discussion. The volume explores:
Keywords: Policy for Science and Technology

China Bound: A Guide to Academic Life and Work in the PRC - Turner-Gottschang, Karen; Reed, Linda A. (The National Academies Press, 1987)
This comprehensive, highly readable handbook simplifies the sometimes complex aspects of day-to-day life in China. Based on the experience of Americans who have recently studied, done research, and taught there, China Bound gives the invaluable "inside" information that only those who have been there can provide. Written primarily for students, scholars, and teachers, the book describes Chinese academic life and work and how Americans can fit into it. And, because it covers such a broad spectrum of topics--from customs regulations, taxation, and medical care to hotel life and how to get laundry done--China Bound is also must reading for anyone who is already planning or just trying to decide whether to plan an extended visit to China. Academic Library Book Review states, "China Bound is one of those books that is absolutely essential."
Keywords: Education

Biographical Memoirs: Volume 88 - National Academy of Sciences (The National Academies Press, 2006)
Biographic Memoirs Volume 88 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 75 - National Academy of Sciences (The National Academies Press, 1998)
Biographical Memoirs is a series of essays containing the life histories and selected bibliographies of deceased members of the National Academy of Sciences. The series provides a record of the life and work of some of the most distinguished leaders in the sciences, as witnessed and interpreted by their colleagues and peers. They form a biographical history of science in America—an important part of our nation's contribution to the intellectual heritage of the world.
Keywords: Biography and Autobiography